The rest is noise : listening to the twentieth century - Ross, Alex 1968- (Farrar, Straus and Giroux, 2007)
The scandal over modern music has not died--while paintings by Picasso and Pollock sell for millions of dollars, works from Stravinsky's Rite of Spring onward still send ripples of unease through audiences. Yet the influence of modern music can be felt everywhere. Avant-garde sounds populate the soundtracks of Hollywood thrillers. Minimalist music has had a huge effect on rock, pop, and dance music from the Velvet Underground onward. Music critic Alex Ross shines a bright light on this secret world, taking us from Vienna before the First World War to Paris in the twenties, from Hitler's Germany and Stalin's Russia to New York in the sixties and seventies. We follow the rise of mass culture and mass politics, of new technologies, of hot and cold wars, of experiments, revolutions, and riots. The end result is not so much a history of twentieth-century music as a history of the twentieth century through its music.--From publisher description.